A Proposal and Simulation with NS3 of a New offloading Algorithm between LTE/LTE-Advanced and Wi-Fi - LYEB, Luc Ange Harry; DEUSSOM DJOMADJI, Eric Michel; TONYE, Emmanuel (European Journal of Applied Sciences, 2022)
The field of mobile telecommunications is an integral part of our society. In the wake of IT, it is implemented and used in all areas of society. This deep anchoring, which mobile networks use today, poses significant problems for operators in terms of speed, capacity demands and customer satisfaction, particularly for the quality of services, but also in terms of profitability and cost of services investments. Reports from Ericsson and Cisco which are representative bases for calculating world total data traffic in cellular mobile networks predict that the number of devices connected to IP networks will be more than three times the global population by 2023. There will be 3.6 networked devices per capita by 2023, up from 2.4 networked devices per capita in 2018. There will be 29.3 billion networked devices by 2023, up from 18.4 billion in 2018. To answer these challenges, two choices are offered to the operators the evolution of the standards or the interconnection of several networks. In this order of idea, we carried out an 4G/4G+ -Wi-Fi offloading simulation algorithm. It was up to us to design an offloading algorithm and then to simulate through a dedicated environment in a scenario allowing to implement it. To achieve this, it was first necessary for us to understand the concept of mobile data offload, to know the types of mobile data offload and to choose one on which the present work will be based. Later we carried out an analysis of the existing data offload algorithms to be able to bring out the limits. From these limits we have designed and proposed a new traffic offloading algorithm with a different approach compared to the existing one studied in the literature. After all this, we have developed and simulated a scenario comprising a 3GPP network in this case the 4G + network, a non 3GPP network in this case the WiFi network, and we have implemented our algorithm via NS3 network simulation software. With this work, we have proposed a solution to overcome an investment deemed expensive to deploy 5G in Africa.